Socially connected while apart: the use of technology to increase social connection between nursing home residents and their relatives - Sehrish Andleeb Akhtar (Frontiers Media S.A., 2024)
IntroductionThis study examines whether the use of a communication technology can enhance social connectedness among nursing home residents in Norway. The concept of social connectedness suggest that positive and significant interpersonal relationships can help reduce the risk of loneliness and social isolation among older adults and can be beneficial for both their health and overall well-being. In recent years, technology has been increasingly utilized as a method to overcome physical distances and to keep families connected. Although the use of digital solutions among older people has increased in recent years, few studies have addressed the use and impact of such technologies within a nursing home context.MethodsA total of 225 residents participated in the study, making it one of the few quantitative studies that examine the use of communication technologies in nursing homes at such a large scale. The study combines two sources of data: (1) survey data collected over a 14-month period, in three different waves, at all public nursing homes in Oslo municipality and (2) a highly detailed weekly datastream from each Komp-device, which provides an objective measure of the frequency of contact between the residents and their families. The two sources of data were combined and analyzed using multiple regression analysis.ResultsThe regression analysis revealed a positive and significant relationship between Komp use and increased social satisfaction among the residents. The results indicate that Komp is a feasible communication tool to help nursing home residents maintain relations with their families.DiscussionThe positive response to Komp among the residents suggests that when designed with the user's needs in mind, technology can indeed facilitate meaningful social interactions, even for those with limited technological experience. Such interventions can thus be crucial in bridging the gap between older residents and the outside world, effectively addressing their unique challenges of social isolation and disconnection from the broader community.